Neighbor Replica Distribution Technique for Cluster Server Systems - Mamat, Rabiei; Mat Deris, Mustafa; Jalil, Mashita (Malaysian Journal of Computer Science, 2004)
Data replication increases the reliability and availability of a web server cluster. However, different data replication techniques have different reliability levels. In this paper, Neighbor Replica Distribution Technique (NRDT) has been proposed to improve the reliability of a web cluster server. This technique provides high reliability by imposing a neighbor logical structure on data copies. Data from one server will be replicated to its neighboring servers and vice versa in the case of failure. The algorithm of NRDT data replica scheme based on the asynchronous replication results in a higher reliability. It shows that this technique provides a convenient approach to high reliability for web server cluster.